1996
DOI: 10.1002/j.1460-2075.1996.tb00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Repair-deficient 3-methyladenine DNA glycosylase homozygous mutant mouse cells have increased sensitivity to alkylation-induced chromosome damage and cell killing.

Abstract: In Escherichia coli, the repair of 3‐methyladenine (3MeA) DNA lesions prevents alkylation‐induced cell death because unrepaired 3MeA blocks DNA replication. Whether this lesion is cytotoxic to mammalian cells has been difficult to establish in the absence of 3MeA repair‐deficient cell lines. We previously isolated and characterized a mouse 3MeA DNA glycosylase cDNA (Aag) that provides resistance to killing by alkylating agents in E. coli. To determine the in vivo role of Aag, we cloned a large fragment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
145
1
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 56 publications
14
145
1
1
Order By: Relevance
“…The contribution of 3MeA DNA glycosylase activity to MMS sensitivity of mammalian cells was more modest but nevertheless significant; MMS doses that allowed approximately 10% survival of the wild type caused less than 1% survival of 3MeA DNA glycosylase-deficient Aag Ϫ/Ϫ null cells (12). Note that there was no detectable 3MeA DNA glycosylase activity in cell extracts made from Aag Ϫ/Ϫ embryonic stem cells, suggesting that the presence of another 3MeA DNA glycosylase with redundant activity is unlikely (12).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of 3MeA DNA glycosylase activity to MMS sensitivity of mammalian cells was more modest but nevertheless significant; MMS doses that allowed approximately 10% survival of the wild type caused less than 1% survival of 3MeA DNA glycosylase-deficient Aag Ϫ/Ϫ null cells (12). Note that there was no detectable 3MeA DNA glycosylase activity in cell extracts made from Aag Ϫ/Ϫ embryonic stem cells, suggesting that the presence of another 3MeA DNA glycosylase with redundant activity is unlikely (12).…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been assumed that N 3 -methyladenine might kill mammalian cells by blocking DNA replication. 13 Conversely, other authors reported that overexpression of MPG was followed by enhanced chemosensitivity to methylating agents, suggesting that apurinic sites, formed as a result of MPG action, might induce sister chromatid exchanges and chromosomal aberrations. 34 In our model system, represented by a leukemic cell line unable to process O 6 -methylguanine, it is reasonable to hypothesize that the cytotoxic and apoptotic effects of the combination of TZM and PADPRP inhibitors might be the consequence of strand interruptions derived from the removal of N-methylpurines and of the resulting apurinic residues.…”
Section: Discussionmentioning
confidence: 99%
“…Aag +/+ and Aag -/-embryonic stem (ES) cells were described previously (21). For these studies, AB1 and clone 65 were used to study wild-type activity (clone 65 was electroporated simultaneously with Aag -/-clones and is of similar passage number).…”
Section: N-[ 3 Hmentioning
confidence: 99%
“…The potential biological relevance of NER activity on methylated bases (20) has not yet been established in vivo. In mammals, the main repair pathway for 3MeA is thought to be BER initiated by the Aag 3MeA DNA glycosylase (alkyladenine DNA glycosylase) (12,21). In addition to 3MeA, Aag is able to remove a broad spectrum of lesions, including 7MeG, hypoxanthine and 1,N 6 -ethenoadenine (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation